Understanding the post-colonial world : theory and method - Chandhoke, Neera; Nehru Memorial Museum and Library (New Delhi : Sterling Publishers, 1994)
Contributed articles.
"Issued under the auspices of the Nehru Memorial Museum and Library."
Includes bibliographical references and index.
Keywords: India -- Politics and government -- 20th century; Great Britain -- Colonies -- History -- 20th century